Urachal cyst abscess in an infant - Antonella Centonze; Domenico Salerno; Stellario Capillo; Aurelio Mazzei; Giuseppe Stranieri (Elsevier, 2019)
Urachal anomalies are rare, in the literature it is reported that the three most common types of urachal anomalies are urachal cysts, urachal sinus, and urachal diverticulum. We present the case of an infant who has come to our observation with painful umbilical mass and purulent discharge, irritability and fever. The suspicion of abscess of urachal sinus was confirmed by ultrasound examination, the VCUG was performed to exclude urinary abnormalities. Surgical removal of urachal sinus was resolutive without complications in follow-up. Keywords: Urachal anomalies, Patent urachus, Urachal abscess, Urachal sinus, Umbilical abscess, Diagnosis, Treatment, Children, Infection